Comparison of Serum Uric Acid-to-HDL Ratio and Triglyceride Glucose Index in Relation to Glycemic Control Among Patients with Type 2 Diabetes Mellitus: Uric Acid and Triglyceride in Type 2 Diabetes Mellitus - Masood, Hafiza Farah; Ain, Qurratul; Lodhi, Hifza Noor; Malik, Bilal Rafique; Sulehri, Faheem Usman; Khushbakht, .; Sikandar, Mirza Zeeshan; Fatima, Sharoona (Pakistan Journal of Health Sciences, 2024)
Diabetes mellitus, which is a case of impaired metabolism related to insulin production or resistance occurs. Serum uric acid levels elevating to some extent were related to diabetes and metabolic syndrome. Hyperuricemia is a serious health risk that may underlie metabolic disorders, such as type 2 diabetes and metabolic syndrome. Objective: To investigate the correlation of uric acid and triglyceride variables with glycemic control in patients with Type 2 Diabetes Mellitus (T2DM). Methods: A Comparative cross-sectional study was conducted on 167 patients categorized into non-diabetic (n=59), diabetic with good glycemic control (n=41), and diabetic with poor glycemic control (n=62) groups. Sociodemographic data and serum variables were recorded. Statistical analysis was performed using SPSS version 26.0, employing one-way ANOVA and Pearson correlation tests. Results: Patients with poor glycemic control exhibited significantly higher fasting blood sugar levels and triglyceride glucose index compared to non-diabetic and well-controlled diabetic individuals. However, there were no significant differences in serum uric acid levels and UHR among the study groups. A positive correlation was observed between the triglyceride glucose index and HbA1c, highlighting the association between intermittent blood glucose rises and worse glycemic outcomes. Conclusion: The triglyceride glucose index revealed the potential to be an inexpensive indicator to evaluate blood sugar levels and should be taken into consideration together with the other generally used indicators like HbA1c to strengthen diabetes management.